Digital Tools and the Flipped Classroom Approach in Primary Education - Loizou, Maria (Frontiers in Education, 2022)
This research aimed to look at the digital tools effectively used in a Flipped Classroom (FC) approach, adopted in five different primary schools in Cyprus, considering the experiences and perceptions of five teachers and 77 students. The FC approach involves the use of digital technologies for developing and sharing flips/tutorials on the content traditionally taught through lecturing in class. Diverse technology tools have been used in FC research together with online learning platforms. Many FC studies have added to the list of essential digital tools, especially the ones which showcase how flips can be developed. However, most of them have not indicated how can these be used for younger students, focusing mainly only in secondary or higher education. Therefore, by collecting the experiences and perceptions of those involved in the primary school process and assessing how the digital tools may or may not promote a positive learning experience could give an indication in how FC can be effectively implemented in primary education. A qualitative research methodology has been adopted by interviewing the five teachers and forming 11 different focus groups of students. Following the thematic analysis. Research results have shown that the most effective digital tools can be categorized into software supporting: (a) Flips; (b) Activities in class; (c) Communication; (d) Entrance tickets; (e) Collaboration; and, (f) Assessment. Overall, a clear illustration of the kind of technology that could be used both at home and in-class for effective FC implementation in primary education is given in the study.